ChemInform Abstract: Using Heteroaryl‐Lithium Reagents as Hydroxycarbonyl Anion Equivalents in Conjugate Addition Reactions with (S, S)‐(+)‐Pseudoephedrine as Chiral Auxiliary; Enantioselective Synthesis of 3‐Substituted Pyrrolidines. Issue 22 (13th May 2013) - Alonso, Beatriz; Ocejo, Marta; Carrillo, Luisa; Vicario, Jose L.; Reyes, Efraim; Uria, Uxue
Abstract A new efficient protocol for the stereocontrolled formation of various 3‐substituted pyrrolidines is presented.